Categorization of Vehicle and Motion Analysis Using Vehicle Features - S.Vanithamai, Ms; S.Purushothaman, Dr (International Journal of Engineering and Technology, 2018)
This research work can identify the vehicle and classify the vehicle using the vehicle features such as shape, color etc., The parameters extracted from the vehicle classification are based on movement of the vehicle are classified as static, movement variation in the successive video frames are used to identify the hazardness of the vehicle. Digital Image processing techniques are used in the object detection. Â